1536 Neuroanatomy, Not Just for Budding Neurosurgeons. Motivations for Participating in An Extra-Curricular Neuroanatomy Course for Undergraduates. (12th October 2021) - Bhate, R; Colman, J; Fowler, T; Hayley, J; Kallam, N; Mak, T L A; Matthews, F; Norton, E; Richardson, D
Abstract: Introduction: Extra-curricular activities form an important part of undergraduate education as they give students the opportunity to explore subjects of interest. There is significant demand within the undergraduate population for further teaching in neuro-related specialities. The aim of this online twelve-week course was to provide neuroanatomy teaching in greater breadth and detail than possible in the undergraduate curriculum. We sought to gauge motivations for involvement. Method: Delegates (n = 166) from six UK universities were asked to complete a short questionnaire examining motivations and future career plans prior to the course beginning, only those who consented were involved further in the analysis (n = 98). Results: Motivations for involvement were predominantly to develop a greater understanding of neuroanatomy (63.3%), to support career plans (13.3%) or to support preparation for an examination or competition (8.2%). The majority (56.1%) had no particular speciality in mind. For those who did, a range of specialities including neurosurgery (24.5%), neurology (8.2%) was given. Conclusions: There is clear interest within the undergraduate population for more specialised extra-curricular activities in addition to conventional experiences such as conferences. Online courses run over multiple weeks provide further scope for depth and exploration of subjects in further detail. In this course, the majority of delegates did not have a particular speciality in mind, demonstrating neuroanatomy to be a popular subject regardless of potential career plans. For students looking to pursue a career in neuro-related specialities, courses are perceived as important opportunities to support future career development.